Beyond Clickbait Islam: Sufistic Da‘wah as a Counter-Model to Religious Commodification in the Digital Age - Khairul Hidayah; Badrah Uyuni; Zamakhsyari Abdul Majid; Sarbini Anim; Mohammad Adnan (International Journal of Emerging Issues in Islamic Studies, 2026)
The expansion of digital media has profoundly transformed contemporary Islamic da‘wah by reshaping religious authority, communication patterns, and audience engagement within algorithm-driven environments. While digital platforms have broadened access to Islamic knowledge, they have also intensified the commodification of religion through visibility-oriented communication characterized by virality, sensationalism, performative piety, and emotional polarization. This study examines Sufistic da‘wah as a communicative counter-model to religious commodification through the case of Habib Umar bin Hafizh. Employing a qualitative case study combined with digital ethnography, the research analysed approximately 40 digital sermons and online religious materials, participant observation, and semi-structured interviews with 15 Indonesian Muslim participants engaged in Sufistic da‘wah communities. The findings suggest that Sufistic da‘wah operates through a communicative framework centered on mahabbah (compassionate love), rifq (gentleness), adab (ethical conduct), and tazkiyat al-nafs (spiritual purification). Participants consistently associated this communication model with emotional calmness, ethical self-reflection, and spiritually meaningful engagement in digital environments. Unlike commodified forms of digital religiosity that prioritize algorithmic visibility and symbolic performance, this paradigm emphasizes spiritual presence, emotional resonance, contemplative engagement, and ethical transformation. The study introduces the concept of spiritual presence as an original analytical framework for understanding religious authority beyond platform visibility and media performance, thereby extending current scholarship on digital religion and Islamic communication. These findings suggest that Sufistic da‘wah offers an ethically grounded model for navigating increasingly mediatized and commodified digital religious environments.